The Effects of Purified Hepatotoxins, Microcystin-LR from Anabaena Circinalis on Some Biochemical Markers of Common Carp (Cyprinus carpio) - Maher M. Khadairi (Journal of Global Pharma Technology, 2017)
Determination the effects of purified microcrystal-LR from Anabaena sp on biochemical markers in liver of C. carpio, Microcrystal-LR was purification by using silica gel, and highly purified and collected by preparative high performance liquid chromatography and concentration of purified hepatotoxins reached to 74.832 µg/ml. fish was intraperitoneally injection with different concentration of microcrystal-LR (3, 6, 9) µg/ kg per day body weight for 30 days. The fish oxidative status was determined through measuring the lipid per oxidation levels MDA, reactive oxygen species ROS and antioxidants activities such as superoxide dismutase SOD, catalase CAT, and glutathione per oxidase GPx and glutathione GSH. The results of presents shown concentration of MDA as well as  ROS and activities of antioxidants such as SOD, CAT and GPx were significantly increased (P<0.05) with increased microcrystal-LR concentration but glutathione activities was significantly decreased with increasing concentration as compared with control groups.Keywords: Hepatotoxins, Microcystin-LR, Purification, Biochemical markers.